Evaluasi Pembelajaran Daring Menggunakan Model Context, Input, Process, Product (CIPP) di SMA Negeri 2 Gerung - Alaydrus, Abdul Kadir (Lembaga Yasin AlSys, 2022)
Online learning requires technology in the learning process and requires adaptation from schools, teachers and students. This very sudden change will require evaluation to see its sustainability. The purpose of this study is to describe the effectiveness of implementing online learning during the covid pandemic at SMAN 2 Gerung using the CIPP model. The research approach used in this study is a qualitative approach. This type of research is a descriptive analysis model that describes the existing problems. Data collection techniques used by researchers are observation, documentation and interviews. The observation used in this study was passive participation, the interviews used were structured interviews and documentation was used to examine the data that had been collected. The results obtained by evaluating the context of the objectives of the online learning system program are quite good. Input evaluation, by implementing a synchronous and asynchronous online learning system for all subjects, has been carried out well. Evaluation of the process of students and educators found that in general the online learning process went well, this was inseparable from the cooperation of educators and students, as well as support from parents. Some students find it difficult in synchronous learning, because of internet costs. The product evaluation explained that the results of online learning were quite good, even though at first the teacher and students experienced difficulties in adjusting learning to use technological media. The interaction of students and educators is going well, seen from a cognitive perspective but from an affective and psychomotor perspective it is not yet effective.